THE UNCONSCIOUS MECHANISMS OF JEALOUSY AND CONTROL: IAGO’S PSYCHOLOGICAL MANIPULATION IN OTHELLO AND ITS CINEMATIC DEPICTIONS - Hasan, Asif (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Iago's manipulation in Othello advances into psychological warfare by utilizing deception techniques that misdirect Othello's understanding and mental perception to achieve rule over him. The research investigates Iago's deceptive techniques by using cognitive psychology and psychoanalysis and social engineering to evaluate his method of control. Freudian and Jungian psychoanalytic perspectives show Iago as someone who projects his suppressed anger and fragmented self-image which matches Dark Triad psychological characteristics. Through textual analysis scholars show how Iago creates mental disharmony in his speeches while comparative film assessments highlight how directors manipulate his character to match contemporary cultural fears about manipulation. The research confirms Iago's position as someone who employs deceptive tactics that today duplicate propaganda methods and modern forms of misinformation alongside media manipulation techniques. Scientists have established villainy as an analytical method to research coercion techniques through deception while studying psychological manipulation patterns which now apply to media studies beside literary formats and behavioural psychology fields. Researchers should investigate both audience reactions to villainous behaviour and scientific methods of studying villainy with an emphasis on digital misinformation techniques. This research uses combined methods from literature studies together with psychology and movies along with social politics to show why Iago remains useful for analyzing manipulation and perceptions today.